Contribution of Sociology Education in Realizing Tolerance and Diversity at SMA Negeri 5 Makassar - Hanafi, Ali; Rudia, Sitti Nasrawati; Saidin, La Ode (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study aims to determine the contribution of sociology education in forming attitudes of tolerance and accepting diversity among students of SMA Negeri 5 Makassar. Through a descriptive qualitative approach, data were collected through observation, interviews with sociology teachers and students, and learning documentation. The results of the study indicate that sociology education plays a strategic role in shaping students' understanding of the importance of living in diversity, respecting differences, and avoiding social conflict. Sociology materials such as social structure, social interaction, and cultural values ​​are the foundation for building students' social awareness. Thus, sociology education makes a positive contribution to creating a harmonious and inclusive school environment.